Calcium scoring. Indicator in the diagnosis of ischemic heart disease - Angela Elvirez Gutierrez; Pedro González Tostón (ECIMED, 2014)
Introduction: The CT scan (64 slices) and coronary calcium test (TCC) can improve risk stratification of patients susceptible to ischemic cardiovascular events. The latter should be integrated in to an overall assessment of cardiovascular risk in order to classify subjects asymptomatic. Objective: Identify the leve lof coronary calcium and evaluate its predictive value and working guidelines regarding the risk obtained. Methods: An observational descriptive cross sectional study was performed.103 patients with asymptomatic coronary disease risk were admitted (70 women, average 57.3 years, range45-74years) in the High Tech Center Sucre state, Venezuela, from March to December 2008. Resulted: Hyperlipidemia group end the majority of patients with a positive coronary calcium test(80.58%). The largest number of patients was stratified with moderate risk of coronary heart disease and low probability of significant coronary artery disease (25.71% for females and 36.36%formales). Conclusions: The predictive value of the test and the guidelines to considering monitoring patients were evaluated. The technique is recommended as a method of coronary calcium screening for coronary risk stratify andselect those with calcified plaques that will benefit from early medical treatment.